Antibody and Complement in Transplant Vasculopathy - Jennifer R. Wehner; Craig N. Morrell; Taylor L. Reynolds; E. René Rodríguez; William M. Baldwin (2007)
Advances in immunosuppression have decreased the incidence of acute rejection, but the development of vasculopathy in the coronary arteries of transplants continues to limit the survival of cardiac allografts. Transplant vasculopathy has also been referred to as accelerated graft arteriosclerosis because it has features of arteriosclerosis, but it is limited to the graft and develops over a period of months to years. Although the pathological features of transplant vasculopathy are well defined, the causative mechanisms are not completely understood. This review focuses on the mechanisms by which antibody and complement can cause or contribute to coronary vasculopathy in cardiac transplants. Antibodies and complement can have independent effects, but the combination of antibodies and complement with inflammatory cells has greater pathogenic potential for the endothelial and smooth muscle cells of the coronary arteries. For example, stimulation through receptors for IgG or complement split products can activate macrophages, but stimulation through combinations of these receptors generates synergistic results. Together, antibodies and complement efficiently integrate the activation of endothelial cells, platelets, and macrophages, which are 3 of the primary components in the pathogenesis of transplant vasculopathy. Recent findings indicate that antibodies and complement produced within the transplant may contribute to vascular pathology in some transplants. Acute rejection caused by antibodies and complement has been treated by combinations of plasmapheresis, intravenous γ -globulin and monoclonal antibodies to CD20 on B lymphocytes. The effect of these treatment modalities on the development of coronary vasculopathy is unknown.